Removal of an endometrioma passing through the left greater sciatic foramen using a concomitant laparoscopic and transgluteal approach: case report - Liang Yanchun; Zhao Yunhe; Xia Meng; Chen Shuqin; Zhu Qingtang; Yao Shuzhong (BMC, 2019)
Abstract Background The combination of intrapelvic and extrapelvic endometriosis is a very rare condition in gynecology. Patients with endometriosis involving the sciatic nerve are easily misdiagnosed because they usually present with atypical symptoms of endometriosis. Here, we present a rare case of an endometrioma passing through the left greater sciatic foramen. Removal of the endometriotic lesion was performed with a concomitant laparoscopic and transgluteal approach through the cooperation of gynecologists and orthopedic (neuro)surgeons. Case presentation A 20-year-old woman presented with complaints of severe dysmenorrhea lasting for more than 6 years and dysfunction of her left lower limb lasting for approximately 4 months. Both CT and MRI demonstrated a suspected intrapelvic and extrapelvic endometriotic cyst (7.3 cm × 8.1 cm × 6.5 cm) passing through the left greater sciatic foramen. Laparoscopic exploration showed a cyst full of dark fluid occupying the left obturator fossa and extending outside the pelvis. A novel combination of transgluteal laparoscopy was performed for complete resection of the cyst and decompression of the sciatic nerve. Postoperative pathology confirmed the diagnosis of endometriosis. Long-term follow-up observation showed persistent pain relief and lower limb function recovery in the patient. Discussion and conclusions When a woman complains of unexplained unilateral sciatica, especially a woman suffering from dysmenorrhea, endometriosis of the sciatica nerve should be considered as a potential etiology. Complete excision of the endometriotic lesion and adequate neurolysis (or decompression) of the sciatic nerve through the multidisciplinary cooperation of experienced gynecologists with proper training in laparoscopic pelvic (neuro)surgery and orthopedic (neuro)surgeons is effective.